Antituberculosis Drugs (Rifampicin and Isoniazid) Induce Liver Injury by Regulating NLRP3 Inflammasomes - Qiang Su; Wei Kuang; Weiyi Hao; Jing Liang; Liang Wu; Chunmei Tang; Yali Wang; Tao Liu (Mediators of Inflammation)
Patients being treated for pulmonary tuberculosis often suffer liver injury due to the effects of anti-TB drugs, and the underlying mechanisms for those injuries need to be clarified. In this study, rats and hepatic cells were administrated isoniazid (INH) and rifampin (RIF) and then treated with NLRP3-inflammasome inhibitors (INF39 and CP-456773) or NLRP3 siRNA. Histopathological changes that occurred in liver tissue were examined by H&E staining. Additionally, the levels IL-33, IL-18, IL-1β, NLRP3, ASC, and cleaved-caspase 1 expression in the liver tissues were also determined. NAT2 and CYP2E1 expression were identified by QRT-PCR analysis. Finally, in vitro assays were performed to examine the effects of siRNA targeting NLRP3. Treatment with the antituberculosis drugs caused significant liver injuries, induced inflammatory responses and oxidative stress (OS), activated NLRP3 inflammasomes, reduced the activity of drug-metabolizing enzymes, and altered the antioxidant defense system in rats and hepatic cells. The NLRP3 inflammasome was required for INH- and RIF-induced liver injuries that were produced by inflammatory responses, OS, the antioxidant defense system, and drug-metabolizing enzymes. This study indicated that the NLRP3 inflammasome is involved in antituberculosis drug-induced liver injuries (ATLIs) and suggests NLRP3 as a potential target for attenuating the inflammation response in ATLIs.